The Use of a Heuristic Problem-Solving Hierarchy to Facilitate the Explanation of Hypothesis-Directed Reasoning - Horvitz, Eric; Heckerman, David; Nathwani, Bharat; Fagan, Lawrence (Elsevier Science Publishers B.V. (North-Holland), 1986)
We examine the problem of explaining expert system recommendations derived from complex reasoning strategies. We focus on the difficulty of justifying advice generated by hypothesis-directed reasoning. In this context, we discuss research on the PATHFINDER system for the diagnosis of lymph node pathology. We present our efforts to manage the complexity of an information optimizing reasoning strategy to facilitate explanation.